Hemophagocytic syndrome and Kaposi sarcoma after liver transplantation - S. E. Voskanyan; V. E. Syutkin; A. P. Mal'tseva; V. S. Rudakov; D. S. Svetlakova; A. A. Davtyan; Z. K. Simavonyan; А. R. Gallyamova; N. A. Probatova; V. R. Gorodetskiy; E. S. Stolyarevich; Yu. D. Udalov; et al. (Трансплантология (Москва), 2018)
Hemophagocytic Syndrome (hemophagocytic lymphohistiocytosis, macrophage activation syndrome) is a rare form of systemic inflammatory response. It usually presents with nonspecific symptoms like fever, lymphoadenopathy, hepatosplenomegaly, cytopenia. Secondary hemophagocytic syndrome is usually associated with severe infection. We describe a clinical case of a patient after liver transplantation who developed hemophagocytic syndrome secondary to Epstein-Barr virus and Human Herpes virus Type 8. There had been 22 cases of hemophagocytic syndrome after liver transplantation described in literature by the moment of our observation. We found just 1 similar case of a patient suffered from hemophagocytic syndrome in combination with Kaposi sarcoma and Epstein Barr virus infection. Differential diagnostics of hemophagocytic syndrome is difficult as there are no specific symptoms. Rapid disease progression makes early diagnosis and treatment an actual problem.